Financial Standing of the Power Sector in Armenia - Kochnakyan, Artur; Zalinyan, Emil (World Bank, Washington, DC, 2016)
The power sector of Armenia achieved remarkable results through first generation policy, legal, regulatory, and institutional reforms implemented from 1991-2003, the first decade of independence. The sector achieved financial sustainability with tariffs that assured recovery of reasonable expenses and collections that reached virtually 100 percent of sales. The implicit and explicit subsidies to the power sector were eliminated and the largest sector companies were among the top taxpayers in the country. More than 70 percent of power sector assets were denationalized (privatized or transferred to Russian ownership in debt-to-asset swaps). However, in 2010 these achievements started to reverse and gradually worsened during the past several years. Today, the large state-owned sector power companies, as well as the privately-owned Electric Networks of Armenia (ENA) have accumulated large amount of expensive commercial debts and are on the verge of bankruptcy.